Nutritional factors associated with aggression - Choy, Olivia (Frontiers in Psychiatry, 2023)
Although the vast majority of patients in forensic psychiatry are treated using pharmacological agents, clinical and ethical concerns about their use have led to the consideration of alternative strategies to reduce aggression that is common in forensic psychiatric settings. One non-invasive and benign biologically-based treatment approach involves nutrition. This article provides a mini-review of the recent evidence on four salient nutritional factors associated with aggressive behavior, namely omega-3 fatty acids, vitamin D, magnesium, and zinc. The current evidence base indicates that lower omega-3 levels are associated with increased aggression. Although research on vitamin D and zinc in relation to aggressive behavior is more limited, there is initial evidence that they are negatively associated with aggression in healthy participants and in psychiatric samples. The relationship between magnesium and aggression varies depending on how magnesium is assessed. Findings from experimental trials reveal that nutritional intervention in the form of omega-3 supplementation has the potential to serve as an effective mode of treatment, with effects that can last beyond the intervention period. There is also support for the utility of nutrition to improve our understanding of how social processes are linked to aggression. In light of the nascent, but promising findings on the role of nutritional factors on aggressive behavior, directions for future research are discussed.